Central bank independence and systemic risk - Alin Marius Andrieș; Anca Maria Podpiera; Nicu Sprincean (Bank of Finland, Institute for Economies in Transition (BOFIT), 2020)
We investigate the relationship of central bank independence and banks' systemic risk measures. Our results support the case for central bank independence, revealing that central bank independence has a robust, negative, and significant impact on the contribution and exposure of a bank to systemic risk. Moreover, the impact of central bank independence is similar for the stand-alone risk of individual banks. Secondarily, we study how the central bank independence affects the impact of selected country and banking system indicators on these systemic measures. The results show that central bank independence may exacerbate the effect of a crisis on the contribution of banks to systemic risk. However, central bank independence seems to mitigate the harmful effect of a bank's high market power on its systemic risk contribution.
URN:NBN:fi:bof-202006162195
Keywords: G21; E58; G28; 330; systemic risk; central bank independence; supervisory framework